2004
DOI: 10.1002/lt.20230
|View full text |Cite
|
Sign up to set email alerts
|

High hilar dissection: New technique to reduce biliary complication in living donor liver transplantation

Abstract: Biliary complications after living donor liver transplantation (LDLT) continue to be problematic. For reducing the biliary complications, the authors applied an intrahepatic Glissonian approach to the recipient hepatectomy. We called this Glissonian dissection technique at the high hilar level high hilar dissection (HHD). In this study, we introduced this HHD technique and evaluated its outcome in 31 recipients of a living donor liver transplant (LDLT). With total occlusion of hepatoduodenal ligament Glissonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 12 publications
0
62
1
2
Order By: Relevance
“…Moreover, the blood supply of the donor as well as the recipient bile duct is critical. Many technical refinements of the donor (93)(94)(95) as well as the recipient operation (96)(97)(98) are aiming at an optimal blood supply of the anastomotic region. In general, during the donor operation the arterial branches to the right respectively left hepatic duct are preserved by sparse dissection of the hepatic artery and especially by avoidance of dissection between the hilar plate and the artery to minimize injury to the communicating artery and the peribiliary plexus (5).…”
Section: Prophylaxis Of Biliary Complications In Ldltmentioning
confidence: 99%
“…Moreover, the blood supply of the donor as well as the recipient bile duct is critical. Many technical refinements of the donor (93)(94)(95) as well as the recipient operation (96)(97)(98) are aiming at an optimal blood supply of the anastomotic region. In general, during the donor operation the arterial branches to the right respectively left hepatic duct are preserved by sparse dissection of the hepatic artery and especially by avoidance of dissection between the hilar plate and the artery to minimize injury to the communicating artery and the peribiliary plexus (5).…”
Section: Prophylaxis Of Biliary Complications In Ldltmentioning
confidence: 99%
“…Hence, it is important to freshen the donor stump as short as possible to maintain adequate blood supply [6]. The high hilar dissection technique in the recipient hepatectomy ensures preservation of the blood supply [2,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…The single right duct is identified in only 50 % of donors [8]. Some studies have indicated that multiple bile ducts in the graft are strongly correlated with a high risk of biliary complications [9].…”
Section: Discussionmentioning
confidence: 99%
“…If there is inadequate bleeding, the bile duct must be shortened. Lee et al 14 introduced a useful technique to prepare the recipient bile duct: a high hilar dissection to provide sufficient length and blood supply of the recipient bile duct. We think this technique is useful especially when preparing a length of recipient bile duct or when multiple duct-to-duct anastomoses are necessary.…”
Section: Discussionmentioning
confidence: 99%